A 57-71-GHz Accurate dB-Linear Variable Gain Power Amplifier with Ultralow Gain Error Using Particle Swarm Optimization Algorithm - Li, Xuwei; Cheng, Depeng; Jiang, Xuhao; Wang, Dongming; Li, Lianming (IEEE MTT-S International Microwave Symposium digest, 2024)
This paper presents a 57-71GHz low-power variable gain power amplifier (VGPA) in a 65nm CMOS process. The proposed VGPA consists of a current-reused variable gain amplifier (VGA) with large accurate dB-linear gain tuning range and a two-stage power amplifier (PA) with high output power and efficiency. To ease calibration and to improve design time efficiency, a particle swarm optimization algorithm (PSO) is utilized to obtain the width of VGA transistors. In particular, this approach can simultaneously achieve the largest gain tuning range, lowest power consumption and lowest RMS gain error for a fixed number of bits. Over 57-71GHz, the measured gain tuning range is 23.5 dB with 0.5-dB step and a peak gain of 22.5 dB. The RMS phase error is from 1.4° to 2.1° and the RMS gain error is less than 0.09 dB over the 3-dB bandwidth. The minimum RMS gain error of 0.05 dB is achieved at 62GHz, demonstrating the best gain accuracy compared to state-of-the-art VGAs. Moreover, the VGPA achieves a peak saturation power (Psat) of 14.4 dBm and a peak power added efficiency (PAE) of 21.5%.